POLIGAMI DALAM KAJIAN SAD DZARI’AH - Idrus, Idrus; Fuadi, Shifriyan (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2020)
Basically in a marriage a man can only have one wife. A woman can only have one husband. Law number 1 of 1974 concerning marriage and the Compilation of Islamic Law provides an opportunity if the male party wishes to have more than one wife, the Court can give permission to a husband who wishes to have more than one wife if the parties wish to do so. One of the objectives of Islamic law is to create benefit and avoid damage (mafsadah). If an action that has not been committed is strongly suspected to cause damage (mafsadah), then things that lead to the action are prohibited. This legal method became known as Sad Zari'ah. The permissibility of polygamy contained in the Marriage Law indirectly, this rule has implemented the concept of sad dzari'ah, because sad dzari'ah itself (generic meaning: closing the road) is preventing an act from causing mafsadah (damage). if an intermediary will cause mafsadah. So the prevention of mafsadah is carried out, because it is forbidden. This is solely for the sake of benefit and rejecting mafsadah (damage) for all citizens in general, and for husband and wife in particular.